External Relations of Entities with Limited Recognition - Baghdasaryan, Mikayel; Trávníčková, Zuzana, 1977-; Halimzai, Pamir; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
Numerous renowned scholars have researched the problem of state recognition. Moreover, the importance of this issue does not need a particular presentation. This paper, will attempt to take yet another look on the subject of state recognition. It will define a state as an actor of international relations. It also will present a theoretical background to the issue of recognition of the states, as it has evolved from the beginning of the past century. By maintaining a descriptive type of qualitative research strategy, followed by normative approach the paper will give a complete overview in terms of theory, but also the practical challenges of obtaining recognition and conducting external relations as an unrecognized state. As a case study, the work will discuss the external relations of Republic of China, Republic of Kosovo and Turkish Republic of Northern Cyprus. The main purpose of this work is to discuss the challenges for unrecognized states and the impact of recognition status on the populations of unrecognized states. The work finds that lack of state recognition makes it almost impossible, for the respective actors, the participation in intergovernmental organizations, which is likely to have a direct impact on the people of the de facto states.
Vedoucí práce: Zuzana Trávníčková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses